FROM TRADITION TO TRANSITION: CHANGING WHEAT AND RICE CULTIVATION IN HARYANA (International Journal of Food and Nutritional Sciences, 2022)
The cropping pattern can be defined as the spatial sequence of cropping under various crops for a given area at a certain time. There have been a lot of changes which have taken place in cropping pattern of Haryana since Green revolution. The Haryana government encouraged the farmers to cultivate Wheat and Rice as a part of this green revolution drive and procure both these crops at MSP. The present paper is attempted to present an analytical account of Wheat and Paddy crops in the state of Haryana. The paper reveals the spatial and temporal variations in both the crops for the time period from period of green revolution to 2019-20. The paper studies the area wise production of both the crops under study. The data has been sourced from Statistical Abstract of Haryana. Secondary data from books, journals, periodicals etc. has been used to draw conclusions for the present paper. The paper finds that the change in cropping pattern of the crops has largely been affected by the changing market- oriented farming of the crops which has in turn, affected the soil fertility, nutritional value of crops and environment as well.